Interplay between RNA-binding protein HuR and microRNA-125b regulates p53 mRNA translation in response to genotoxic stress. Issue 11 (1st November 2016) - Ahuja, Deepika; Goyal, Ashish; Ray, Partho Sarothi
ABSTRACT: Tumor suppressor protein p53 plays a crucial role in maintaining genomic integrity in response to DNA damage. Regulation of translation of p53 mRNA is a major mode of regulation of p53 expression under genotoxic stress. The AU/U-rich element-binding protein HuR has been shown to bind to p53 mRNA 3′UTR and enhance translation in response to DNA-damaging UVC radiation. On the other hand, the microRNA miR-125b is reported to repress p53 expression and stress-induced apoptosis. Here, we show that UVC radiation causes an increase in miR-125b level in a biphasic manner, as well as nuclear cytoplasmic translocation of HuR. Binding of HuR to the p53 mRNA 3′UTR, especially at a site adjacent to the miR-125b target site, causes dissociation of the p53 mRNA from the RNA-induced silencing complex (RISC) and inhibits the miR-125b-mediated translation repression of p53. HuR prevents the oncogenic effect of miR-125b by reversing the decrease in apoptosis and increase in cell proliferation caused by the overexpression of miR-125b. The antagonistic interplay between miR-125b and HuR might play an important role in fine-tuning p53 gene expression at the post-transcriptional level, and thereby regulate the cellular response to genotoxic stress.